Self-reinforcing and self-undermining feedbacks in subnational climate policy implementation. Issue 5 (29th July 2021) - Millar, Heather; Bourgeois, Eve; Bernstein, Steven; Hoffmann, Matthew
ABSTRACT: This study demonstrates how interpretive feedback functions as an intervening mechanism during policy implementation that helps explain variation in subnational climate policy entrenchment. We examine three interrelated climate policy processes in Ontario, Canada from 2001–2018: a coal phase-out (2001–2014), the feed-in-tarriff (FIT) program for renewable energy (2006–2013) and a cap-and-trade program (2008–2018). Successful framing of the coal phase-out in terms of gains for both public health and climate change helped generate a broad-based coalition of support during implementation. Conversely, we find that the FIT and the cap-and-trade programs were vulnerable to framing around losses, especially regarding electricity rates and household costs, which counter-coalitions used to weaken public support during implementation. Our analysis demonstrates that building supportive coalitions for climate policy goes beyond the material gains and losses generated by initial policy designs. Framing strategies interact with policy designs over time to support or undermine policy durability.